The Effect of Organizational Commitment, Interpersonal Communication, and Motivation on Employee Satisfaction and Performance - Sukmawati Sukmawati; Palipada Palisuri; Muhlis Ruslan; Indrayani Nur (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study was to determine and analyze the effect of organizational commitment, interpersonal communication, and motivation on employee satisfaction and performance at the South Sulawesi Government Hospital. The population in this study were all employees at the South Sulawesi Government Hospital, totaling 1,912 people. Determination of the previous sample using the techniqueStratified Random Sampling or also called stratified random sampling. Stratified Random Sampling of as many as 243 respondents. The analytical model used in this research is a quantitative and descriptive structural Equation Model (SEM) using the AMOS program. The results of this study are Organizational Commitment and Work Motivation have a positive and significant effect on job satisfaction, while Interpersonal Communication has a negative but significant effect on job satisfaction. Organizational Commitment has a positive but not significant effect on job satisfaction and Interpersonal Communication has a negative but significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Organizational Commitment has a positive and significant influence on Employee Performance through Job Satisfaction. Has a significant effect on performance through the mediation of organizational commitment. Interpersonal communication has a negative but significant effect on employee performance mediated by job satisfaction and motivation has a positive and significant effect on employee performance mediated by job satisfaction